2017
DOI: 10.1093/jamia/ocx107
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient safety and efficiency of medication reconciliation through the development and adoption of a computer-assisted tool with automated electronic integration of population-based community drug data: the RightRx project

Abstract: Background and ObjectiveMany countries require hospitals to implement medication reconciliation for accreditation, but the process is resource-intensive, thus adherence is poor. We report on the impact of prepopulating and aligning community and hospital drug lists with data from population-based and hospital-based drug information systems to reduce workload and enhance adoption and use of an e-medication reconciliation application, RightRx.MethodsThe prototype e-medical reconciliation web-based software was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 32 publications
1
33
0
2
Order By: Relevance
“…Another study reported more positive results, demonstrating that use of the electric tool improved compliance with the MedRec process from 34% to 98%–100% 16. The same result was also reported by Tamblyn et al 25 the overall medication reconciliation completion rate was 88.1% (1242/1410) in the software intervention units compared with 46.3% (698/1506) in the control units.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Another study reported more positive results, demonstrating that use of the electric tool improved compliance with the MedRec process from 34% to 98%–100% 16. The same result was also reported by Tamblyn et al 25 the overall medication reconciliation completion rate was 88.1% (1242/1410) in the software intervention units compared with 46.3% (698/1506) in the control units.…”
Section: Resultssupporting
confidence: 67%
“…The publication year ranged from 2006 to 2017. A total of nine studies were carried out in the USA13–21 (69.2%), while the other three studies were performed in Spain22–24 and one in Canada 25. Only three studies13 18 25 were RCTs (23.1%).…”
Section: Resultsmentioning
confidence: 99%
“…A BPMH could not be obtained for complex patients with extensive medication histories or for those with incomplete information. The development of a computer‐assisted tool with automated electronic integration of patient‐based medication data was useful to accelerate the procedure of medication reconciliation, improve efficiency, and ensure that patients use medications safely . Previous research has reported that the PharmaCloud system facilitates accurate and efficient medication reconciliation by pharmacists for patients with polypharmacy (≥5 medications), to provide a medication therapy management service .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of a medication-related problem rests on an accurate medication history; yet, accessing community pharmacy patient medication lists can be challenging. One medication reconciliation initiative13 addressed this existing barrier to accurate diagnosis by automatically bringing community pharmacy records to the provider, helping the adopter to efficiently detect medication-related problems.…”
Section: Relative Advantagementioning
confidence: 99%
“…Schnipper et al 1 report two sites with an increase in medication discrepancies after implementing new electronic health records. By contrast, Tamblyn et al 13 undertook extensive software customisation and design to meet the needs of users trying to complete medication reconciliation, then provided small group training by local champions. This innovative package (some of which included new technology) was associated with a ninefold increase in the odds of completing medication reconciliation, with the most marked impact of the intervention being in the surgical units, with completion rates of 80.7% in the intervention unit compared with 0.7% in the control units 13…”
Section: Technical Supportmentioning
confidence: 99%